"The obligation of newspeople is not only to give the news accurately; it is also to say it correctly": Production and perception of broadcaster speech. (12th July 2015) - Strelluf, Christopher
Abstract : This research explores the popular belief among Americans that broadcasters speak a 'correct' version of American English. Six broadcast journalism students and six non journalism students recorded news stories as if they were 'on radio or television'. Their readings are examined auditorily for intervocalic-/t/ flapping, coronal stop deletion, variable (ng), and allegro gonna-wanna. Samples of speech from interviews with the students are also examined for comparison between tasks. Results show that students being trained as broadcasters do not meet the popular expectation for producing prescriptively standard speech, suggesting that these sociolinguistic variables operate consistently across speakers and refuting folk perceptions about broadcaster speech. News readings are also ranked and commented on by listeners for perceived professionalism. Respondents are generally able to differentiate trained broadcasters from other speakers. Rankings do not reward prescriptivist productions. Respondents are also less consistent in ranking African American speakers for professionalism than they are white speakers.